The psychological toll of food insecurity - Alloush, Mo; Bloem, Jeffrey R. (Elsevier, 2022)
We investigate the relationship between food insecurity and psychological distress among a sample of poor households in Lebanon. We first document large unconditional differences in various measures of psychological distress based on whether a respondent lives in a household experiencing acute food insecurity. Next we show that these differences persist even when accounting for heterogeneity by interview timing, geography, and other characteristics. Considering results across a variety of regression specifications, we find that experiencing acute food insecurity increases scores on a psychological distress index by at least 0.16 standard deviations. These results carry implications for the literature on the mental health consequences of food insecurity and poverty alleviation policy.